2013
DOI: 10.13065/jksdh.2013.13.06.987
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pain experience upon dental fear

Abstract: Objectives : The aim of the study is to offer basic data that help to reduce dental fear by measuring adult dental fear level with DFS scale. Methods : The subjects were 300 persons including college students in W University and their parents in Jeollabuk-do Province. Data were collected by convenience sampling from May 1 to May 30, 2013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, it can cause physical and psychological pain in some patients 18) . Ju and Park 19) stated that the main cause of patients' avoidance of dental treatment was pain experienced during past treatment, and Park et al 18) stated that a method is needed to reduce patients' pain during dental scaling. de Jongh and Stouthard 20) reported that patients experience a great deal of anxiety due to the noise and vibrations generated during dental scaling, and the anxiety can lead to pain during treatment 21) .…”
Section: Key Results and Comparison With Previous Studiesmentioning
confidence: 99%
“…However, it can cause physical and psychological pain in some patients 18) . Ju and Park 19) stated that the main cause of patients' avoidance of dental treatment was pain experienced during past treatment, and Park et al 18) stated that a method is needed to reduce patients' pain during dental scaling. de Jongh and Stouthard 20) reported that patients experience a great deal of anxiety due to the noise and vibrations generated during dental scaling, and the anxiety can lead to pain during treatment 21) .…”
Section: Key Results and Comparison With Previous Studiesmentioning
confidence: 99%
“…Sharp syringes, the sound of rotary instruments, and other sharp tools used in dental procedures can make individuals more susceptible to fear and anxiety [33]. Moreover, it was revealed that pain experiences resulting from dental pain and insufficient anesthesia experience had a marked influence on dental fear levels [38]. It could be helpful to better understand the mechanisms of orofacial pain perception by determining the detailed effects of contributing factors for the establishment of a more effective pain control strategy.…”
Section: Discussionmentioning
confidence: 99%
“…5, 2018 320 felt more fear due to higher level and frequency of pain in previous dental treatments. Grant et al 15) reported that fear and pain are felt when the dental instrument is inserted into the periodontal pocket without anesthesia during scaling, which is related to fear and anxiety, and that dental fear was greater when pain was directly experienced 16) . Hence, reducing this dental fear and pain during scaling can be assumed to be very important in the prevention of oral diseases.…”
Section: Introductionmentioning
confidence: 99%